Analisis Swot Dan Identifikasi Faktor-Faktor Yang Membuat Siswa Tertarik Mendaftar Ke Program Studi Bisnis Digital - Lilla Rahmawati; Rico Elhando Badri; M. Ariza (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2022)
The Study Program Digital Business is a new program at IIB Darmajaya which was formed to answer the challenges of industry 4.0 which is thick with digital technology. Based on the trend of the digital economy which is growing rapidly every time. This study seeks to find out what factors are significant in attracting high school students or equivalent so that they can choose to enroll in the Digital Business Program using the Cochran Q Test method. Based on the results of this study, it was found that 5 attributes truly describe the level that students consider the most in determining the decision to choose the Study Program. Based on the results of this factor analysis, the Marketing Bureau at IIB Darmajaya can create a specific marketing campaign on these 5 attributes and have successfully identified the strengths, weaknesses, opportunities, and threats of the Program. Digital Business. This analysis, the Program Digital Business can continue to improve student competencies by increasing their flight hours in the field to produce new startups. While maintaining the quality of the curriculum, human resources, and infrastructure in accordance with the times.